Diseño de un plan comercial para la promoción del complejo turístico Platanales, cantón Bolívar - Álava Chichanda, Paola Gabriela (2014)
The research was conducted to study aimed to design a business plan for the resort Platanales. For this purpose, a methodology is divided into four phases structured, such as: a situational diagnosis of the situation where the tourist site Platanales georeferencing and analyzed, also includes analysis Platanales resort where an internal analysis was performed, external and strategic location, the structure of the business plan and budget of the same, considering the literature review of projects related to the study topic. Structuring the business plan included the development of the goals, mission and vision, and likewise strategies, furthermore proceeded to annex the inventory tab site Platanales, the design of the tourism brand for the complex were structured and signage of the area where the project will be located. The tour marks the same as was done by graphic designer Luis Palacios, signaling the project site, advertising brochures, and promotion on the web: Also an advertising plan which identified four projects was developed. The results of the study required by the Autonomous Government of the Canton Municipal Decentralization Bolívar to market the resort Platanales and thus strengthen tourism in Bolívar and surroundings were also determined. With this research it was demonstrated that the implementation and execution of the business plan for the resort Platanales through advertising offered and designed for this work is feasible.